Enhancing manufacturing efficiency: A case study on automotive assembly line balancing techniques for improving production capacity - Abdul Rasib, Amir Hamzah; Abdullah, Rohana; Wahyono, F. F.Zubaidi; Ramli, Mohd Irman (Taylor's University, 2025)
The automotive Assembly Line Balancing Problem (ALBP) is a classic NP-hard combinatorial optimization problem. The ALBP is the process of maximizing the distribution of jobs or workstations in an automotive Assembly Line (AL) in the automotive industry to reduce idle time for employees and equipment and guarantee that the output of production meets demand while keeping the required quality level. The objective of this study is to identify the cause of the unbalanced AL, apply the ALB technique to increase the capacity of the current AL, and eventually propose improvements that should be made to the current assembly by allocating the necessary number of workers in the AL and figuring out the appropriate processing time for the various processes. This study categorizes objectives into identification, data collection and analysis, and method of improvement. A literature review serves as a reference for the study, drawing on validated sources in the field. The collected data were then analysed to propose an improvement method by conducting a time study methodology in ALB and determining the optimum number of workstations in the AL. A significant finding from this research is the effect of implementing ALB in AL, such as standard time, process flow, and optimum number of workstations in the assembly process. The outcome of this study will be presented to automotive manufacturing companies. This study improves the productivity of AL and improves the working conditions by assigning optimal task distribution in the workstation. The outcomes provide practical insights for professionals to optimize production capacity, streamline operations, and gain a competitive edge.